Stability of Thermophilic Pig Manure Mono-digestion: Effect of Thermal Pre-treatment and Separation - Vergote, Tine L. I.; De Dobbelaere, Anke E. J.; Willems, Bernard; Leenknegt, Jan; Buysse, Jeroen; Volcke, Eveline I. P.; Meers, Erik (Frontiers in Energy Research, 2020)
Anaerobic pig manure digestion holds potential to contribute to a bio-based economy. This work assesses the stability of the thermophilic mono-digestion process. Thermophilic mono-digestion experiments with (i) fresh liquid pig manure and (ii) the fresh fecal fraction from source separation by a pig housing construction were conducted in semi pilot-scale continuous stirred tank reactors. The effect of separation on the digestion stability was studied by comparing thermophilic mono-digestion of fresh liquid (unseparated) and fresh source separated pig manure. Influencing factors and inhibitors were identified during the experiments. An unstable thermophilic mono-digestion process was observed for fresh liquid pig manure at a digester retention time of 60 days, due to high levels of ammonia and sulfur-containing components. Thermophilic mono-digestion of the fresh fecal fraction was more promising in terms of stability, provided enough time for digestion. In addition, the effect of low temperature (70°C) thermal pre-treatment of manure on the digestion stability was investigated. In the case of liquid pig manure, no improvement in the digestion stability was noted upon thermal pre-treatment. For the fecal fraction, the stability of the thermophilic mono-digestion process did improve. Moreover, thermal treatment and subsequent thermophilic mono-digestion of the fresh fecal fractions from two different farms with a similar pig housing construction suggested an effect of the (organic) dry matter content on the process stability.